Analysis of the Use of the SOFA Score in Predicting Mortality among Critically III Patients - Putra, Reyshar Pratama; Subandi, Andi; Sari, Putri Irwanti; Nurhusna, Nurhusna; Oktarina, Yosi (Inspirasi Foundation, 2026)
Introduction: Sepsis is one of the main causes of morbidity and mortality in critical patients in the Intensive Care Unit (ICU). Delays in identifying organ dysfunction are an important factor that increases the risk of death. The Sequential Organ Failure Assessment (SOFA) Score is an assessment tool that is widely used to measure the extent of organ damage and predict mortality in sepsis patients. Objective: To know the output results of sepsis and sepsis shock patients and which indicators of the SOFA Score affect the patient's output. Methods: Quantitative research with a retrospective cohort design with a total population of 102 patients with a sample of 53 patients assisted by scoring assessment using the MDCalc application. Results: overall output experienced mortality with the indicators that affected the SOFA Score score, namely; MAP, FiO2, Ventilator Use, Billirubin, and GCS. Other indicators that affect output include; RR, Glucose, and Leukocytes. Conclusion: This study confirms that SOFA Score can be used as an effective prediction tool to assess the prognosis of sepsis patients, as well as sepsis shock so that it can assist health workers in clinical decision-making and therapy planning more appropriately.